Predictive potential of angiopoietin-2 in a mCRC subpopulation treated with vanucizumab in the McCAVE trial - Ferreira, Cláudia S.; Babitzki, Galina; Klaman, Irina; Krieter, Oliver; Lechner, Katharina; Bendell, Johanna; Vega Harring, Suzana; Heil, Florian (Frontiers in Oncology, 2023)
Introduction Angiopoetin-2 (Ang-2) is a key mediator of tumour angiogenesis. When upregulated it is associated with tumour progression and poor prognosis. Anti-vascular endothelial growth factor (VEGF) therapy has been widely used in the treatment of metastatic colorectal cancer (mCRC). The potential benefit of combined inhibition of Ang-2 and VEGF-A in previously untreated patients with mCRC was evaluated in the phase II McCAVE study (NCT02141295), assessing vanucizumab versus bevacizumab (VEGF-A inhibitor), both in combination with mFOLFOX-6 (modified folinic acid [leucovorin], fluorouracil and oxaliplatin) chemotherapy. To date, there are no known predictors of outcome of anti-angiogenic treatment in patients with mCRC. In this exploratory analysis, we investigate potential predictive biomarkers in baseline samples from McCAVE participants. Methods Tumour tissue samples underwent immunohistochemistry staining for different biomarkers, including Ang-2. Biomarker densities were scored on the tissue images using dedicated machine learning algorithms. Ang-2 levels were additionally assessed in plasma. Patients were stratified by KRAS mutation status determined using next generation sequencing. Median progression-free survival (PFS) for each treatment group by biomarker and KRAS mutation was estimated using Kaplan–Meier plots. PFS hazard ratios (and 95% confidence intervals) were compared using Cox regression. Results Overall low tissue baseline levels of Ang-2 were associated with longer PFS, especially in patients with wild-type KRAS status. In addition, our analysis identified a new subgroup of patients with KRAS wild-type mCRC and high levels of Ang-2 in whom vanucizumab/mFOLFOX-6 prolonged PFS significantly (log-rank p=0.01) by 5.5 months versus bevacizumab/mFOLFOX-6. Similar findings were seen in plasma samples. Discussion This analysis demonstrates that additional Ang-2 inhibition provided by vanucizumab shows a greater effect than single VEGF-A inhibition in this subpopulation. These data suggest that Ang-2 may be both a prognostic biomarker in mCRC and a predictive biomarker for vanucizumab in KRAS wild-type mCRC. Thus, this evidence can potentially support the establishment of more tailored treatment approaches for patients with mCRC.